Good enough : 40ish devotionals for a life of imperfection - Bowler, Kate; Richie, Jessica (Convergent, 2022)
"A compassionate, intelligent, and wry series of Christian daily reflections on learning to live with imperfection in a culture of self-help that promotes endless progress, from the New York Times bestselling author of Everything Happens for a Reason and the executive producer of the Everything Happens podcast. In Kate Bowler's bestselling memoir Everything Happens for a Reason, readers witnessed the ways she, as a divinity-school professor and young mother, reckoned with a Stage IV cancer diagnosis; in her follow-up memoir, No Cure for Being Human, she unflinchingly and winsomely unpacked the ways that life becomes both hard and beautiful when we abandon certainty and the illusion of control in our lives. Now, in their first-ever devotional book, Kate Bowler and co-author Jessica Richie offer 40ish short spiritual reflections on how we can make sense of life not as a pursuit of endless progress but as a chronic condition. This book is a companion for when you want to stop feeling guilty that you're not living your best life now. Written gently and with humor, Good Enough is permission for all those who need to hear that there are some things you can fix-and some things you can't. And it's okay that life isn't always better. In these gorgeously written reflections, Bowler and Richie offer fresh imagination for how truth, beauty, and meaning can be discovered amid the chaos of life. Their words celebrate kindness, honesty, and interdependence in a culture that rewards ruthless individualism and blind optimism. Ultimately, in these pages we can rest in the encouragement to strive for what is possible today-while recognizing that though we are finite, the life in front of us can be beautiful."--